Gradient Hölder regularity for degenerate parabolic systems. (December 2022) - Bögelein, Verena; Duzaar, Frank; Liao, Naian; Scheven, Christoph
Abstract: We establish the local Hölder regularity of the spatial gradient of weak solutions to a class of general, degenerate parabolic systems. Our results can be regarded as a generalization of the fundamental work by DiBenedetto and Friedman (1985).